Transthyretin cardiac amyloidosis in patients after TAVR: clinical and echocardiographic findings and long term survival. (26th October 2021) - Shimoni, Sara; Zikri, Meital; Haberman, Dan; Livschitz, Shay; Tshori, Sagi; Fabricant, Yacov; Meledin, Valery; Gandelman, Gera; Goland, Sorel; George, Jacob
Abstract: Aims: The aim of this study was to examine the prevalence of amyloid transthyretin (ATTR) cardiac amyloidosis in patients 1–2 years after trans‐catheter aortic valve replacement (TAVR) and to assess their clinical and echocardiographic outcome and long‐term survival. Methods and results: We enrolled 88 patients, mean age 81 years, 534 (390–711) days after TAVR. Patients underwent a Tc99m‐PYP scintigraphy for the diagnosis of ATTR cardiac amyloidosis. Eleven (12.5%) participants were diagnosed with ATTR cardiac amyloidosis. Eighty eight per cent of patients without amyloidosis were in New York Heart Association Classes 1–2 after TAVR, compared with 64% patients with ATTR cardiac amyloidosis ( P  = 0.022). There were no differences in left ventricular (LV) ejection fraction ( P  = 0.69) between patients with and without ATTR cardiac amyloidosis at enrolment. The LV mass index and pulmonary artery pressure were significantly higher in patients with ATTR cardiac amyloidosis ( P  = 0.046 and P  = 0.002, respectively). Global longitudinal strain and myocardial work efficiency were significantly lower in patients with ATTR cardiac amyloidosis ( P  = 0.031 and P  = 0.048, respectively). We assessed changes in echocardiographic data, from the time of TAVR to enrolment, and as expected, there was a significant decrease in aortic valve gradient in both groups. There was a significant reduction in LV mass and LV mass index and improvement in basal segment LV strain in the ATTR cardiac amyloidosis negative group ( P  = 0.045, P  = 0.046 and 0.023, respectively). However, in the ATTR cardiac amyloidosis group the change in LV mass and LV mass index and LV basal strain values was not significant ( P  = 0.24, P  = 0.13 and P  = 0.35, respectively). The were no significant changes in other echocardiographic parameters in both groups. The patients were followed for 1150 (1086–1221) days after enrolment. Twenty seven patients had at least one cardiac hospitalization during of follow up, of them seven were with ATTR cardiac amyloidosis and 20 patients without amyloidosis ( P  = 0.017). Eighteen patients (20%) died during follow up; 12 (14%) patients died due to cardiac causes. There was no difference in all‐cause and cardiac mortality between patients with and without ATTR cardiac amyloidosis ( P  = 0.6 and P  = 0.53, respectively). Conclusions: The long‐term survival after TAVR is not significantly affected by the presence of ATTR cardiac amyloidosis. However, the clinical course of these patients and the LV hemodynamic improvement is less favourable. This hypothesis‐generating study suggests screening for ATTR cardiac amyloidosis in patients who underwent TAVR and have limited clinical or echocardiographic improvement, because they may potentially improve with new therapies for ATTR cardiac amyolidosis.